Digital Numbers Constructed by Fine Patterned Polydopamine on DNA Templates. Issue 21 (2nd September 2021) - Zhang, Meizhou; Wang, Shuangshuang; Li, Longjie; Li, Mengran; Cheng, Xinyi; Shi, Yiwei; Wu, Yuzhou
Abstract: Using DNA nanostructures as templates to synthesize shape‐controlled polydopamine (PDA) is a promising strategy to realize the fabrication of exquisite PDA nanomaterials. However, previous studies using small DNA tiles as templates could only afford very simple structures such as lines and crosses due to the limited space on the template and the relatively low resolution of the PDA nanopatterns. Therefore, the best resolution of the PDA nanostructures that can be achieved by this technique is carefully investigated. And by connecting several DNA tiles together, larger DNA templates are built up and achieve the synthesis of complicated digital nanopatterned PDA structures. Abstract : Polydopamine (PDA) nanostructures with designed patterns, such as digital numbers, are prepared by DNA‐templated in situ synthesis. A handful of guidelines about DNA template selection and structure resolution design are provided for fabricating the desired structure with this method. This paper demonstrates the potential of sophisticated PDA fabrication on DNA templates.